(untitled) (Anales de la Real Academia de Medicina y Cirugía de Valladolid, 2024)
Until Organic Law 2/2010 on sexual and reproductive health and voluntary termination of pregnancy (LOSSR, 2010), there was no legal regulation (yes, jurisprudence) of health conscientious objection. Article 19.2 indicated that only health professionals directly involved in abortion could exercise this right in advance and in writing. There was no mention of the registers of objectors. Between the 2010 and 2021 LOSSR, there were two important milestones as a result of regulatory provisions issued by the Communities of Castilla-La Mancha and Navarre. In development of the 2010 law, these two Autonomous Communities launched two registries where conscientious objectors to abortion can be registered.